An L-shaped link between the composite dietary antioxidant index and human papillomavirus infection in women: a US population-based study - Li, Yuhua; Zheng, Yulin; Zhao, Jinhua; Cao, Yuanyuan; Meng, Xiaofei; Liu, Xiaoyan; Wang, Xiaolan; Zhang, Lili (Frontiers in Nutrition, 2025)
ObjectiveThis study intended to inspect the link between a comprehensive dietary antioxidant index (CDAI) and human papillomavirus (HPV) infection in US women.MethodsThe link between CDAI and HPV infection was analyzed by weighted univariate and multivariate regression models, restricted cubic spline (RCS), and subgroup analyzes using the NHANES data from 2003 to 2016.ResultsData from 8,115 subjects were included, with a weighted prevalence of HPV infection of 38.01%. After adjusting for all covariates, HPV infection decreased by 2% for each 1-unit rise in CDAI [(95%CI: 0.96, 0.99), p = 0.042]. RCS results elicited a non-linear link (P-non-linear = 0.043). VE and zinc intake were negatively linked to HPV infection (both p < 0.05). Subgroup analysis noted a notable interaction of marital status in the link between CDAI and HPV infection (P for interaction = 0.011).ConclusionCDAI is negatively linked to HPV infection. American women can enhance their intake of antioxidant-rich foods, especially those rich in zinc and vitamin E, to reduce HPV infection risk and enhance antioxidant defenses.